Rapid climate changes in the arctic region of Svalbard - Dahlke, Sandro (M. Sc.) (2020)
Over the last decades, the Arctic regions of the earth have warmed at a rate 2–3 times faster than the global average– a phenomenon called Arctic Amplification. A complex, non-linear interplay of physical processes and unique pecularities in the Arctic climate system is responsible for this, but the relative role of individual processes remains to be debated. This thesis focuses on the climate change and related processes on Svalbard, an archipelago in the North Atlantic sector of the Arctic, which is shown to be a "hotspot" for the amplified recent warming during winter. In this highly dynamical region, both oceanic and atmospheric large-scale transports of heat and moisture interfere with spatially inhomogenous surface conditions, and the corresponding energy exchange strongly shapes the atmospheric boundary layer. In the first part, Pan-Svalbard gradients in the surface air temperature (SAT) and sea ice extent (SIE) in the fjords are quantified and characterized. This analysis is based on observational data from meteorological stations, operational sea ice charts, and hydrographic observations from the adjacent ocean, which cover the 1980–2016 period. It is revealed that typical estimates of SIE during late winter range from 40–50% (80–90%) in the western (eastern) parts of Svalbard. However, strong SAT warming during winter of the order of 2–3K per decade dictates excessive ice loss, leaving fjords in the western parts essentially ice-free in recent winters. It is further demostrated that warm water currents on the west coast of Svalbard, as well as meridional winds contribute to regional differences in the SIE evolution. In particular, the proximity to warm water masses of the West Spitsbergen Current can explain 20–37% of SIE variability in fjords on west Svalbard, while meridional winds and associated ice drift may regionally explain 20–50% of SIE variability in the north and northeast. Strong SAT warming has overruled these impacts in recent years, though. In the next part of the analysis, the ...